MORPHOLOGICAL AND IMMUNOHISTOCHEMICAL DIAGNOSTIC OF GASTROINTESTINAL STROMAL TUMORS OF THE DIGESTIVE TRACT - D.M. Nahorna; O.G. Kuryk; V.O. Yakovenko; V.V. Bazdyrev (Bogomolets National Medical University, 2016)
Gastrointestinal stromal tumors (GIST) are the most common mesenchymal tumors of the gastrointestinal tract arising from interstitial cells of Cajal, mainly in the stomach and small intestine. GIST have oncogenic mutations in KIT or PDGFRA gene in 85-90% of tumors. For diagnostic GIST is nessesary to use immunohistochemistry with specific labeled antibodies that stained molecule CD117 (c-kit). Other possible diagnostic markers of GIST are CD34, DOG-1, desmin, vimentin, MSA, S100. Ki-67 is a marker for the determination of the There is a possibility to diagnose GIST in stomach and intestinal tract at the early stage of progression with further endoscopic minimally invasive treatment. A retrospective evaluation of the results of diagnostics and mini-invasive treatment of GIST on the basis of the Medical Center "Oberig" during 2008-2015 years were analyzed. Before surgery all patients underwent esophago- gastroduodenoscopy, videocolonoscopy and endoscopic enteral biplane ultrasound examination to exclude the possibility of invasion. 10 cases of non-epithelial tumors of gastrointestinal tract were diagnosed by endoscopic way: 8 (80%) of them - GIST and 2 (20%) leiomyomas. GIST were localized: 4 (50%) in stomach, 2 (12,5%) - in small intestine, 1 (12,5%) - in ascending colon, 2 (25%) - in rectum. Leiomyomas were found in esophagus. All tumors were removed by endoscopic submucosal dissection within healthy tissue, which was confirmed by morpho logical examination. We used the immunohistochemical markers for diagnostic of gastrointestinal stromal tumors and leiomyomas and for determination the malignancy potential of GIST.